Comportamiento mecánico de las inclusiones - González, J. C.; de Castillo, T. G.; Sáenz López, A.; Hey, Alfredo Martín (Comisión Nacional de Energía Atómica; Argentina, 1976)
Fil: González, J. C. Comisión Nacional de Energía Atómica; Argentina